2006
DOI: 10.1590/s1413-70542006000400024
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de lisina para frangos de corte nos períodos de 22 a 42 e de 43 a 49 dias de idade

Abstract: RESUMOForam realizados dois experimentos para determinar a exigência de lisina total para frangos de corte Ross, macho, no período de 22 a 42 e de 43 a 49 dias de idade. Utilizou-se em cada experimento, 900 frangos com peso médio inicial de 764 g ± 35 g aos 22 dias e de 2520 ± 73 g aos 43 dias de idade. As aves foram distribuídas em um delineamento inteiramente casualizado, com seis tratamentos, seis repetições e 25 aves por unidade experimental. Os tratamentos foram constituídos de seis níveis lisina, de acor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
3
5
0
1
Order By: Relevance
“…The average yield carcass in this study in both slaughter (70 days = 68.61% and 84 days = 70.82%) were higher than those reported by Madeira et al (2010) at 84 days of age to three free-range lineage, Master Griss (67.95%), Label Rouge (68.99%) and Red Heavy (69.82%). The linear increase for breast yield obtained in this study in chickens slaughtered at 84 days of age are in agreement with the results of Costa et al (2006). However, Takahashi et al (2006) found no significant differences in free-range chickens slaughtered at 70 and 84 days old, although there was difference in relation to these chickens from Ross lineage that got higher yield.…”
Section: Effects Of Different Lysine Values On Carcass Characteristicssupporting
confidence: 90%
“…The average yield carcass in this study in both slaughter (70 days = 68.61% and 84 days = 70.82%) were higher than those reported by Madeira et al (2010) at 84 days of age to three free-range lineage, Master Griss (67.95%), Label Rouge (68.99%) and Red Heavy (69.82%). The linear increase for breast yield obtained in this study in chickens slaughtered at 84 days of age are in agreement with the results of Costa et al (2006). However, Takahashi et al (2006) found no significant differences in free-range chickens slaughtered at 70 and 84 days old, although there was difference in relation to these chickens from Ross lineage that got higher yield.…”
Section: Effects Of Different Lysine Values On Carcass Characteristicssupporting
confidence: 90%
“…(8) The lowest abdominal fat levels were obtained with 1.28% dietary lysine ( Figure 5). The obtained abdominal fat results are consistent with the findings of Barboza et al (2000) and Costa et al (2006). Almeida et al (2002) found that increasing dietary lysine levels up to 1.00% allow for the reduction of abdominal fat in broilers.…”
Section: Valériosupporting
confidence: 91%
“…(4) Those authors stressed that lysine levels should not be lower than 1.10% or a total of 29.6 grams during the finisher phase (35 to 47 days). Costa et al (2006) also reported that feed conversion ratio improved with increasing lysine levels, as described by the first order (p<0.01) equation: FC = 1.57+ 0.29 lysine levels (R 2 = 0.75) eq. (5) Nascimento (2003) found that increasing dietary lysine levels promoted higher muscle deposition and weight gain, and reduced abdominal fat, leading to better feed conversion ratio.…”
Section: Goulartmentioning
confidence: 91%
“…Positive effect of increase in the dietary lysine levels, with or without supplementation of industrial amino acids, on the FC of growing broilers has been reported by several researchers (Leclercq et al, 1998;Rezaei et al, 2004;Lana et al, 2005;Costa et al, 2006;Assis et al, 2008;Balbino et al, 2008;Viola et al, 2009a;Ghahri et al, 2010).…”
Section: Resultsmentioning
confidence: 83%